Mineral loss and color change of enamel after bleaching and staining solutions combination - Napoleao de Araujo, Larissa Sgarbosa; Santos, Paulo Henrique dos [UNESP]; Anchieta, Rodolfo Bruniera [UNESP]; Catelan, Anderson; Briso, André Luiz Fraga [UNESP]; Soares Fraga Zaze, Ana Carolina; Sundfeld, Renato Herman [UNESP] (Spie-soc Photo-optical Instrumentation Engineers, 2013)
Pigments of food and beverages could affect dental bleaching efficacy. The aim of this investigation was to evaluate color change and mineral loss of tooth enamel as well as the influence of staining solutions normally used by adolescent patients undergoing home bleaching. Initial hardness and baseline color were measured on enamel blocks. Specimens were divided into five groups (n = 5): G1 (control) specimens were kept in artificial saliva throughout the experiment (3 weeks); G2 enamel was exposed to 10% carbamide peroxide for 6 h daily, and after this period, the teeth were cleaned and stored in artificial saliva until the next bleaching session; and G3, G4, and G5 received the same treatments as G2, but after bleaching, they were stored for 1 h in cola soft drink, melted chocolate, or red wine, respectively. Mineral loss was obtained by the percentage of hardness reduction, and color change was determined by the difference between the data obtained before and after treatments. Data were subjected to analysis of variance and Fisher's test (a = 0.05). G3 and G5 showed higher mineral loss (92.96 +/- 5.50 and 94.46 +/- 1.00, respectively) compared to the other groups (p = 0.05). G5 showed high-color change (9.34 +/- 2.90), whereas G1 presented lower color change (2.22 +/- 0.44) (p = 0.05). Acidic drinks cause mineral loss of the enamel, which could modify the surface and reduce staining resistance after bleaching. (C) 2013 Society of Photo-Optical Instrumentation Engineers (SPIE)
Keywords: tooth bleaching; enamel; color; spectrophotometry; hardness; carbamide peroxide